2021
DOI: 10.1093/ckj/sfab152
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response to a third injection of BNT162b2 vaccine in patients on maintenance haemodialysis

Abstract: Background Humoral response against SARS-CoV-2 after two doses of BNT162b2 (Pfizer-BioNTech) has been proven less intense in maintenance dialysis patients as compared to healthy subjects, leading the French authorities to recommend a third injection in this population. Here, we investigated the response to the third injection in two cohorts of hemodialysis patients. Methods Data from two prospective observational cohorts were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 25 publications
6
46
0
1
Order By: Relevance
“…This suggestion is also supported by a recent report on hemodialysis patients, in which homologous ChAd/ChAd vaccination induced lower SARS-CoV-2-spike-IgG-levels in COVID-19-naïve hemodialysis patients than homologous BNT/BNT vaccination [ 30 ]. Also, in a recent study of hemodialysis patients, a third dose of BNT162b2 allowed seroconversion in more than half of non-responders [ 31 ] or enhanced humoral response in almost all hemodialysis patients. Dialysis patients with low humoral response may benefit from a third dose of BNT162b2 mRNA COVID-19 vaccine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is also supported by a recent report on hemodialysis patients, in which homologous ChAd/ChAd vaccination induced lower SARS-CoV-2-spike-IgG-levels in COVID-19-naïve hemodialysis patients than homologous BNT/BNT vaccination [ 30 ]. Also, in a recent study of hemodialysis patients, a third dose of BNT162b2 allowed seroconversion in more than half of non-responders [ 31 ] or enhanced humoral response in almost all hemodialysis patients. Dialysis patients with low humoral response may benefit from a third dose of BNT162b2 mRNA COVID-19 vaccine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the very low titers in KTR are alarming, not only regarding the potential of vaccines to protect against COVID-19 disease, but also the longevity of the supposed protection. Several trials have already reported on immune responses to a third vaccine dose in KTR non-responders [ 28 , 29 , 30 ] and weak responders [ 31 ], as well as HD patients [ 32 , 33 ]. Approximately 50% of KTR developed a positive AB response after a third dose.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to an increasing number of breakthrough infections ( Shroff et al, 2021 ; Juno and Wheatley, 2021 ; Goldberg et al, 2021 ; Fowlkes et al, 2021 ; Davidovic et al, 2021 ; Campo et al, 2021 ). Currently, several countries have developed various strategies to tackle this problem, among which, additional doses of COVID-19 vaccines have shown to be safe and efficient in boosting immune response ( Yue et al, 2021 ; Falsey et al, 2021 ; Dekervel et al, 2021 ; Choi et al, 2021 ; Barros-Martins et al, 2021 ). Nonetheless, the low vaccination rate, coupled with the risk of emergence of vaccine-resistant SARS-CoV-2 variants and waning immunity, emphasizes the burning need to develop novel drugs and therapeutic modalities for COVID-19 ( Artese et al, 2020 ; Twomey et al, 2020 ; Drożdżal et al, 2020 ).…”
Section: Vaccinesmentioning
confidence: 99%